“INVESTIGATION OF THE EFFICIENCY IMPACT OF IRRIGATION REGIMES ON COTTON GROWTH AND DEVELOPMENT” - Ashurova Gulmira Aminovna (TADQIQOTLAR, 2025)
Cotton does not consume the same amount of water at all stages of growth, setting a specific water and nutrient regime for each phase of its development, taking into account the interaction between soil, water and plant need Violation of the interdependence slows down the growth of the plant, slows its development and delays the passage of the basic phases.